2021
DOI: 10.1155/2021/5587817
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research of the Influence of Microfracture Morphology on Permeability of Shale Rock

Abstract: Hydraulic fracturing is currently one of the main technical methods of shale gas exploitation. The permeability variation of shale gas reservoir after fracturing is inevitable, while the influence of fracture length and fracture width on permeability and seepage characteristics of shale rock is a mystery. Besides, the stress sensitivity characteristics of shale rock, derived from different initial permeability, with the same permeability after fracturing are also ambiguous. To this end, a series of seepage cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Research on the accumulation and occurrence characteristics of coal-measure source rocks of Junggar Basin in Xinjiang Province was carried out by means of drilling, outcrop, and experimental tests [10][11][12][13][14][15]. Quantitative fluorescence technology was used to conduct fluorescence analysis on shale, tight reservoir, and crude oil of the Lukou Formation, and indicated that hydrocarbons in the upper section have better physical properties and higher thermal maturity.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the accumulation and occurrence characteristics of coal-measure source rocks of Junggar Basin in Xinjiang Province was carried out by means of drilling, outcrop, and experimental tests [10][11][12][13][14][15]. Quantitative fluorescence technology was used to conduct fluorescence analysis on shale, tight reservoir, and crude oil of the Lukou Formation, and indicated that hydrocarbons in the upper section have better physical properties and higher thermal maturity.…”
Section: Introductionmentioning
confidence: 99%